A Retroperitoneal Leiomyosarcoma Presenting as an Adrenal Incidentaloma in a Subject on Warfarin - Ishrat N. Khan; Mohamed A. Adlan; Michael J. Stechman; Lakdasa D. Premawardhana (Case Reports in Endocrinology)
Adrenal incidentalomas (AIs) are mostly benign and nonsecretory. Management algorithms lack sensitivity when assessing malignant potential, although functional status is easier to assess. We present a subject whose AI was a retroperitoneal leiomyosarcoma (RL). Case Presentation. A woman on warfarin with SLE and the antiphospholipid syndrome, presented with left loin pain. She was normotensive and clinically normal. Ultrasound scans demonstrated left kidney scarring, but CT scans revealed an AI. MRI scans later confirmed the AI without significant fat and no interval growth. Cortisol after 1 mg dexamethasone, urinary free cortisol and catecholamines, plasma aldosterone renin ratio, and 17-hydroxyprogesterone were within the reference range. Initially, adrenal haemorrhage was diagnosed because of warfarin therapy and the acute presentation. However, she underwent adrenalectomy because of interval growth of the AI. Histology confirmed an RL. The patient received adjuvant radiotherapy. Discussion. Our subject presented with an NSAI. However, we highlight the following: (a) the diagnosis of adrenal haemorrhage in this anticoagulated woman was revised because of interval growth; (b) the tumour, an RL, was relatively small at diagnosis; (c) this subject has survived well over 60 months despite an RL perhaps because of her acute presentation and early diagnosis of a small localised tumour.